2016
DOI: 10.3847/2041-8205/831/1/l10
|View full text |Cite
|
Sign up to set email alerts
|

A Model of White Dwarf Pulsar Ar Scorpii

Abstract: A 3.56-hour white dwarf (WD) -M dwarf (MD) close binary system, AR Scorpii, was recently reported to show pulsating emission in radio, IR, optical, and UV, with a 1.97-minute period, which suggests the existence of a WD with a rotation period of 1.95 minutes. We propose a model to explain the temporal and spectral characteristics of the system. The WD is a nearly perpendicular rotator, with both open field line beams sweeping the MD stellar wind periodically. A bow shock propagating into the stellar wind accel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 32 publications
11
66
1
Order By: Relevance
“…The double peak structure in optica/UV bands of AR Sco is similar to the Crab pulsar (isolated young neutron star), for which the electrons/positrons are accelerated by the electric field parallel to the magnetic field line, where the charge density deviates from the Goldreich-Julian charge density. As pointed out by Geng et al (2016), however, the number of the particles that emit the observed pulse optical emissions of AR Sco is significantly larger than the number that can be supplied by the WD itself. This suggests that the synchrotron emitting electrons are supplied from the Mtype star surface, and the acceleration process is different from that of NS pulsars.…”
Section: Spectrum Of the Pulsed Componentmentioning
confidence: 98%
See 2 more Smart Citations
“…The double peak structure in optica/UV bands of AR Sco is similar to the Crab pulsar (isolated young neutron star), for which the electrons/positrons are accelerated by the electric field parallel to the magnetic field line, where the charge density deviates from the Goldreich-Julian charge density. As pointed out by Geng et al (2016), however, the number of the particles that emit the observed pulse optical emissions of AR Sco is significantly larger than the number that can be supplied by the WD itself. This suggests that the synchrotron emitting electrons are supplied from the Mtype star surface, and the acceleration process is different from that of NS pulsars.…”
Section: Spectrum Of the Pulsed Componentmentioning
confidence: 98%
“…AR Sco's broadband electromagnetic spectrum from radio to UV bands is characterized by a synchrotron radiation from relativistic electrons, indicating acceleration process in the binary system. As pointed out by Geng et al (2016), on the other hand, the number of particles that emits the observed pulsed optical emission of AR Sco is significantly larger than the number that can be supplied by the WD itself. Geng et al (2016) thus suggest that an electron/positron beam from the WD's polar cap sweeps the stellar wind from the M-type star, and a bow shock propagating into stellar wind accelerates the electrons in the wind.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…At higher frequencies, ν ≥ few × 10 14 Hz (optical-UV-X-rays), the SED follows a different ν α 2 power law [1], where α 2 ∼ −0.2 (see also [3]). This component is produced by non-thermal synchrotron emission from accelerated charged particles as the magnetic white dwarf dipole interacts with the M-star magnetic field and wind, and can explain the high level of linear polarization observed at optical frequncies.…”
Section: Interpretation and Proposed Modelmentioning
confidence: 99%
“…The high level of polarization also led Buckley et al [2] to conclude that the white dwarf is highly magnetic, with a field strength as high as 500 MG. Various interpretations have been proposed to explain the observed properties, including direct MHD interactions between the magnetic fields of both components [2], possibly producing bow shocks close to the surface of the M-star companion (e.g., [3,4]). …”
Section: Introductionmentioning
confidence: 99%